1986
DOI: 10.1620/tjem.148.341
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of anti-.ALPHA.-fetoprotein antibody for radioimmunodetection: Analysis with .ALPHA.-fetoprotein-secreting rat hepatoma and antigen-bound acrylic beads.

Abstract: Using AFP-secreting AH66 rat hepatoma cells and AFP-bound acrylic beads (AFP-B), artificial cells expressing surface antigen, the effect of blood AFP level on the accumulation of radiolabeled rabbit anti-AFP antibody in the site of tumor and beads implanted in rats was examined. Scintigrams of hepatoma-bearing rats with implanted AFP-B showed a marked localization in AFP-B site, but not in the tumor site on day 5 after the injection of radiolabeled antibody. The imaging of AFP-B was most satisfactory in normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
1989
1989

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Because AFP is rapidly exported from malignant hepatocytes after synthesis and is not expressed on the cell membrane, it is unlikely that AFP antibody would localize to these cells to an appreciable extent, an observation confirmed by Tanno et al (5). In the study of Koji and his colleagues (2), 30 to 60% of total AFP antibody radioactivity in a tumor homogenate was present in the fraction which contained nuclei and cell membranes (2), which would not have been expected with an export protein.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Because AFP is rapidly exported from malignant hepatocytes after synthesis and is not expressed on the cell membrane, it is unlikely that AFP antibody would localize to these cells to an appreciable extent, an observation confirmed by Tanno et al (5). In the study of Koji and his colleagues (2), 30 to 60% of total AFP antibody radioactivity in a tumor homogenate was present in the fraction which contained nuclei and cell membranes (2), which would not have been expected with an export protein.…”
Section: Discussionmentioning
confidence: 78%
“…Unlike carcinoembryonic antigen, which is expressed on the cell membrane and has been successfully imaged in tumor tissue, AFP is actively secreted by malignant hepatocytes and is found in the cytosol of these cells. Using an experimental model, Tanno et al (5) have recently shown poor localization of AFP antibody to malignant hepatocytes containing cytosolic AFP, but good localization to beads which had been coated with AFP and then embedded in rat tissues. Furthermore, the extremely high serum AFP concentrations which may be encountered in patients with HCC (greater than lo6 ng per ml in some instances) may, because of extensive immune complex formation in the plasma, prevent the AFP antibody from reaching the tumor.…”
mentioning
confidence: 99%